1999
DOI: 10.1006/dbio.1999.9372
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse Cer1 (Cerberus related or homologue) Gene Is Not Required for Anterior Pattern Formation

Abstract: Cer1 is the mouse homologue of the Xenopus Cerberus gene whose product is able to induce development of head structures during embryonic development. The Cer1 protein is a member of the cysteine knot superfamily and is expressed in anterior regions of the mouse gastrula. A segmental pattern of expression with nascent and newly formed somites is also seen. This suggests an additional role in development of the axial skeleton, musculature, or peripheral nervous system. Xenopus animal cap assays and mouse germ-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…However, this model has not been demonstrated conclusively by loss-of-function analysis (Simpson et al 1999;Belo et al 2000;Shawlot et al 2000). When cerberus mRNA is microinjected into early Xenopus embryos, ectopic heads (as marked by eye and cement gland) are formed in ∼36% of the embryos (Fig.…”
Section: Rar and Head Induction By Cerberusmentioning
confidence: 99%
“…However, this model has not been demonstrated conclusively by loss-of-function analysis (Simpson et al 1999;Belo et al 2000;Shawlot et al 2000). When cerberus mRNA is microinjected into early Xenopus embryos, ectopic heads (as marked by eye and cement gland) are formed in ∼36% of the embryos (Fig.…”
Section: Rar and Head Induction By Cerberusmentioning
confidence: 99%
“…Unlike its Xenopus counterpart, mouse Cerl-1 does not bind Wnt and inhibit Wnt signaling (Belo et al 2000) and is not essential for mouse head formation (Table 1) (Simpson et al 1999;Belo et al 2000;Shawlot et al 2000;Stanley et al 2000). Rather, Cerberus-related proteins are key regulators of Nodal signaling and play an important role in the establishment of left -right asymmetry in the vertebrate embryo (Rodriguez Esteban et al 1999;Yokouchi et al 1999;Zhu et al 1999;Hashimoto et al 2004;Marques et al 2004;Tavares et al 2007;Vonica and Brivanlou 2007).…”
Section: Cerberusmentioning
confidence: 99%
“…We found that Cerberus is not induced by Wnt antagonists, but others have shown it and mouse Cerberus-like to be up-regulated by Nodal (Ding et al 1998;Brennan et al 2001;Norris et al 2002;Yamamoto et al 2003). Although mouse Cerberus-like differs importantly from Xenopus Cerberus in its inability to bind Wnt (Belo et al 2000), functional overlap between Hex and Cerberus or Cerberus-like might reinforce heart induction in Xenopus but constitute sufficient redundancy to cause only structural malformations in Hex mutant mice and perhaps contribute to absence of a heart phenotype in Cerberus-like mutants (Simpson et al 1999;Belo et al 2000;Shawlot et al 2000).…”
Section: Hex In the Context Of Heart-inducing Pathwaysmentioning
confidence: 99%